Long non-coding (lnc)RNA profiling and the role of a key regulator lnc-PNRC2-1 in the transforming growth factor-β1-induced epithelial–mesenchymal transition of CNE1 nasopharyngeal carcinoma cells. Issue 3 (March 2021) - Yang, Jie; Feng, Enzi; Ren, Yanxin; Qiu, Shun; Zhao, Liufang; Li, Xiaojiang
Objectives: To identify key long non-coding (lnc)RNAs responsible for the epithelial–mesenchymal transition (EMT) of CNE1 nasopharyngeal carcinoma cells and to investigate possible regulatory mechanisms in EMT. Methods: CNE1 cells were divided into transforming growth factor (TGF)-β1-induced EMT and control groups. The mRNA and protein expression of EMT markers was determined by real-time quantitative PCR and western blotting. Differentially expressed genes (DEGs) between the two groups were identified by RNA sequencing analysis, and DEG functions were analyzed by gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses. EMT marker expression was re-evaluated by western blotting after knockdown of a selected lncRNA. Results: TGF-β1-induced EMT was characterized by decreased E-cadherin and increased vimentin, N-cadherin, and Twist expression at both mRNA and protein levels. Sixty lncRNA genes were clustered in a heatmap, and mRNA expression of 14 dysregulated lncRNAs was consistent with RNA sequencing. Knockdown of lnc-PNRC2-1 increased expression of its antisense gene MYOM3 and reduced expression of EMT markers, resembling treatment with the TGF-β1 receptor inhibitor LY2109761. Conclusion: Various lncRNAs participated indirectly in the TGF-β1-induced EMT of CNE1 cells. Lnc-PNRC2-1 may be a key regulator of this and is a potential target to alleviate CNE1 cell EMT.